Students' perception and expectation of service quality at UiTM Kuala Pilah / Haslinda Ab Malek, Isnewati Ab Malek and Noreha Mohamed Yusof - Ab Malek, Haslinda; Ab Malek, Isnewati; Mohamed Yusof, Noreha (2012)
The students of higher education have increased rapidly. Students are the most important customer of a university. Therefore, a university should make sure that, it has a high quality education system and should also provide a proper learning environment in order to enhance the learning process. Based on these grounds, this study was conducted in order to determine students' perception and expectation of service quality at the UiTM Kuala Pilah. Besides, the focus of this research is to measure a gap between the perceptions and expectations using a modified SERVQUAL instruments. The 500 questionnaires were distributed to the students and analyzed by using SPSS Software. A descriptive study was undertaken to investigate the students' perceptions and expectations of service quality at the UiTM Kuala Pilah. The finding shows high reliability (Cronbach's coefficient alpha=0.738) to all items in the modified questionnaires. An analysis of mean gap score was obtained by subtracting the expectation score from the corresponding perception score to find out the students' satisfaction with each of the factors. The study shows that students' expectations of service quality exceeded their perceptions on each items in the questionnaire. It showed that the gap of all dimension of service quality were negative. Based on the paired sample t-test analysis, the result shows that there is a statistically significant difference between the perceptions and expectations for most of the dimensions. Thus, improvements are required across all the dimension of service quality in UiTM Kuala Pilah in order to meet the students' satisfaction.